2012
DOI: 10.1364/josab.29.003259
|View full text |Cite
|
Sign up to set email alerts
|

Photonic generation of high-frequency microwave signals utilizing a multi-transverse-mode vertical-cavity surface-emitting laser subject to two-frequency orthogonaloptical injection

Abstract: We study photonic microwave signal generation obtained when single-and multi-transverse-mode vertical-cavity surface-emitting lasers (VCSELs) are subject to two-frequency orthogonal optical injection. Our calculations show that broadly tunable microwave signals can be obtained in these systems. The response of the multi-transversemode VCSEL is enhanced with respect to that obtained with a similar single-transverse-mode VCSEL subject to the same two-frequency orthogonal optical injection. The extra degree of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Vertical-cavity surface-emitting lasers (VCSELs) have many desired features, such as circular beam profile, single-longitudinal mode operation, ease of fabrication, low power consumption and low-cost, therefore could be an excellent candidate for microwave photonic signal generation [14]. Quirce et al predict that microwave photonic signal can be generated using a multi-mode VCSEL subject to two frequency orthogonal optical injection [15]. In 2015, 20 GHz microwave photonic signal was obtained using double-beam orthogonal optical injection in a single-transverse-mode VCSEL [16].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical-cavity surface-emitting lasers (VCSELs) have many desired features, such as circular beam profile, single-longitudinal mode operation, ease of fabrication, low power consumption and low-cost, therefore could be an excellent candidate for microwave photonic signal generation [14]. Quirce et al predict that microwave photonic signal can be generated using a multi-mode VCSEL subject to two frequency orthogonal optical injection [15]. In 2015, 20 GHz microwave photonic signal was obtained using double-beam orthogonal optical injection in a single-transverse-mode VCSEL [16].…”
Section: Introductionmentioning
confidence: 99%
“…The use of off-the-shelf VCSELs therefore offers a method to achieve low-cost and low power consumption of photonic microwave generation. In recent years, photonic microwave generation using VCSEL has drawn a great deal of attention [18][19][20][21][22][23]. More than 20 GHz photonic microwave signal has been obtained using dual-beam orthogonal optical injected in a single-transverse-mode VCSEL [23], however, no significant reduction of the linewidth is achieved by using double injection because the linewidth is mainly determined by the phase fluctuations of the two master lasers.…”
Section: Introductionmentioning
confidence: 99%
“…In this second experiment the polarization of the injected light is orthogonal to that of the free-running slave VCSEL. The theoretical study of this case has shown that the microwave signal generation mechanism is independent of the polarization of the master lasers [15]. Our results show that the VCSEL can emit in the two master laser frequencies.…”
Section: Introductionmentioning
confidence: 56%
“…Very recently, microwave generation using dual-beam optical injection in semiconductor lasers has also been investigated [6], [11][12][13][14][15]. Microwave signals with frequencies corresponding to the frequency difference between the master lasers can be generated [6], [11], [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation